NCIS origins. Season 1 [videorecording (DVD)] - Monreal, Gina Lucita; North, David J. (Screenwriter) (Paramount, 2025)
Begins in 1991, years prior to the events of NCIS and follows a young Leroy Jethro Gibbs, narrated by Mark Harmon. In the series, Gibbs starts his career as a newly minted special agent at the fledgling NCIS Camp Pendleton office where he forges his place on a gritty, ragtag team led by NCIS legend Mike Franks.